Recovery from 6‐month spaceflight at the International Space Station: muscle‐related stress into a proinflammatory setting. Issue 4 (8th January 2019) - Capri, Miriam; Morsiani, Cristina; Santoro, Aurelia; Moriggi, Manuela; Conte, Maria; Martucci, Morena; Bellavista, Elena; Fabbri, Cristina; Giampieri, Enrico; Albracht, Kirsten; Flück, Martin; Ruoss, Severin; et al.
ABSTRACT: The Sarcolab pilot study of 2 crewmembers, investigated before and after a 6‐mo International Space Station mission, has demonstrated the substantial muscle wasting and weakness, along with disruption of muscle's oxidative metabolism. The present work aimed at evaluating the pro/anti‐inflammatory status in the same 2 crewmembers (A, B). Blood circulating (c‐)microRNAs (miRs), c‐proteasome, c‐mitochondrial DNA, and cytokines were assessed by real‐time quantitative PCR or ELISA tests. Time series analysis was performed ( i.e ., before flight and after landing) at 1 and 15 d of recovery (R+1 and R+15, respectively). C‐biomarkers were compared with an age‐matched control population and with 2‐dimensional proteomic analysis of the 2 crewmembers' muscle biopsies. Striking differences were observed between the 2 crewmembers at R+1, in terms of inflamma‐miRs (c‐miRs‐21‐5p, ‐126‐3p, and ‐146a‐5p), muscle specific (myo)‐miR‐206, c‐proteasome, and IL‐6/leptin, thus making the 2 astronauts dissimilar to each other. Final recovery levels of c‐proteasome, c‐inflamma‐miRs, and c‐myo‐miR‐206 were not reverted to the baseline values in crewmember A. In both crewmembers, myo‐miR‐206 changed significantly after recovery. Muscle biopsy of astronaut A showed an impressive 80% increase of α‐1‐antitrypsin, a target of miR‐126‐3p. These results point to a strong stress response induced by spaceflight involving muscle tissue and the proinflammatory setting, where inflamma‐miRs and myo‐miR‐206 mediate the systemic recovery phase after landing.—Capri, M., Morsiani, C., Santoro, A., Moriggi, M., Conte, M., Martucci, M., Bellavista, E., Fabbri, C., Giampieri, E., Albracht, K., Flück, M., Ruoss, S., Brocea, L., Canepari, M., Longa, E., Di Giulio, I., Bottinelli, R., Cerretelli, P., Salvioli, S., Gelfi, C., Franceschi, C., Narici, M., Rittweger, J. Recovery from 6‐month spaceflight at the International Space Station: muscle‐related stress into a proinflammatory setting. FASEB J. 33, 5168–5180 (2019). www.fasebj.org